1991
DOI: 10.1530/jrf.0.0920281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reducing the remating interval after parturition on the fertility and plasma concentrations of luteinizing hormone, prolactin, oestradiol-17  and progesterone in lactating domestic rabbits

Abstract: Primiparous crossbred does were remated on Day 1 (n = 15) or 14 (n = 25) post partum and killed on Day 10 post coitum to assess their fertility. Blood samples were taken during the pre- (0-12 h post coitum) and post- (1-10 days post coitum) ovulatory periods and plasma was assayed for luteinizing hormone (LH), prolactin, oestradiol-17 beta and progesterone. Ovulation response was significantly greater (P less than 0.01) and ovulation rate significantly lower (P less than 0.001) in does mated on Day 1 than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…However, in our study, estradiol levels were similar in both weaned and lactating does. The origin of lower progesterone levels remains unknown but several hypotheses can be made: 1) the action of estrogen is regulated by a placental luteotrophic hormone (Gadsby and Keyes, 19841, placentas were lighter in the L group than in the W group; consequently, compromised secretion of placental luteotropin may contribute to decreased progesterone concentrations; 2 ) prolactin is required to sustain pregnancy in the rabbit (Hilliard, 19731, whereas high levels of prolactin decreased progesterone production in rabbit (Lin et al, 1987) and therefore progesterone production may be lowered during lactation; 3 ) progesterone production in the rabbit CL is dependent on lipoprotein-delivered cholesterol (Holt, 19891, the mammary gland is a site that uses lipoproteins for milk production (Guesnet and Demarne, 1987) and therefore the supply of lipoproteins to the ovary may not meet the requirements for optimal luteal steroidogenesis in lactating does; and 4 ) the high feed intake that occurs during lactation may alter the metabolic turnover rate of progesterone and influence its peripheral concentration (Symonds and Prime, 1989;Lamb et al, 1991). Whatever the origin, it can be proposed that lower progesterone levels lead to higher fetal mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study, estradiol levels were similar in both weaned and lactating does. The origin of lower progesterone levels remains unknown but several hypotheses can be made: 1) the action of estrogen is regulated by a placental luteotrophic hormone (Gadsby and Keyes, 19841, placentas were lighter in the L group than in the W group; consequently, compromised secretion of placental luteotropin may contribute to decreased progesterone concentrations; 2 ) prolactin is required to sustain pregnancy in the rabbit (Hilliard, 19731, whereas high levels of prolactin decreased progesterone production in rabbit (Lin et al, 1987) and therefore progesterone production may be lowered during lactation; 3 ) progesterone production in the rabbit CL is dependent on lipoprotein-delivered cholesterol (Holt, 19891, the mammary gland is a site that uses lipoproteins for milk production (Guesnet and Demarne, 1987) and therefore the supply of lipoproteins to the ovary may not meet the requirements for optimal luteal steroidogenesis in lactating does; and 4 ) the high feed intake that occurs during lactation may alter the metabolic turnover rate of progesterone and influence its peripheral concentration (Symonds and Prime, 1989;Lamb et al, 1991). Whatever the origin, it can be proposed that lower progesterone levels lead to higher fetal mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Previous workers have shown that occurrence of ovulation (Foxcroft and Hasnain, 1973), ovulation rate (Harned and Casida, 1969;Lamb et al, 1991), and fertilization of oocytes (Torres et al, 1977) are lower in lactating than in nonlactating does. Effects of lactation on embryonic and fetal mortality are controversial.…”
Section: Introductionmentioning
confidence: 96%
“…It is worthy noting that pre‐mating PRL level in all groups has pronounced positive relationship with reproductive performance, being the best with the highest pre‐mating PRL level. Pre‐mating plasma prolactin concentrations were 15.5 and 16.3 ng/ml in non‐ovulating and no mated rabbit does (Lamb et al, ). During pregnancy, circulating levels of PRL show a gradual rise in all groups to reach a maximum at mid‐pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Mating produces an immediate surge of LH (Carlson, Wong and Perrin, 1977 ;Mills et al, 1983 ;Iwai et al, 1991 ;Lamb et al, 1991), which induces progesterone production (Mills and Gerardot, 1984). LH dramatically increases 30 min after coitus (Kanematsu et al, 1974) and reaches its highest value after 90-120 min ; 12 hr after mating, it returns to precoital levels (Waterston and Mills, 1976 ;Mills and Gerardot, 1984 ;Osteen and Mills, 1979).…”
Section: Discussionmentioning
confidence: 99%